Prevalent factors of career uncertainties among Ghanaian senior high school students (Journal of Educational Management, 2023)
Research has shown that career uncertainty is a major issue that distorts the career trajectories of many adolescents, specifically senior high school students, as many of them are unable to make career decisions that will place them on a firm path of career development. The study explored the most prevalent factors of career uncertainty related to Ghanaian high school students. The research design employed was a descriptive survey, and 426 students were selected for participation by means of multi-stage sampling. Data were gathered with a four-point Likert-type scale questionnaire on career uncertainty for senior high school students. Data analysis was done using descriptive statistics. The results depicted that, among all the factors investigated to determine the career uncertainty of senior high school students, self-awareness, fear and anxiety in decision-making, inadequate career information, inadequate career counselling, peer pressure, family interference, and academic accomplishment challenges were the most prevalent factors of career uncertainty. The recommendations made were that school guidance coordinators need to be sensitive to issues of self-awareness, fear, and anxiety in decision-making, inadequate career information, inadequate career counselling, peer pressure, family interference, and academic accomplishment challenges throughout counselling sessions to facilitate well-informed and wise career decisions. It was recommended that all stakeholders in Ghana’s educational sector collaborate to formulate and implement policies that encourage students to plan, develop, and make career choices before the end of their high school years.
Keywords: Career Uncertainty; Prevalent; Senior High School Students